Synthesis Of Nanostructured TiO2 Thin Films By Pulsed Laser Deposition (PLD) And The Effect Of Annealing Temperature On Structural And Morphological Properties - Al-Obaidi, Sarmad Sabih; Yousif, Ali Ahmed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work, nanostructured TiO2 thin films were grown by pulsed laser deposition (PLD) technique on glass substrates. TiO2 thin films then were annealed at 400-600 Â°C in air for a period of 2 hours. Effect of annealing on the structural and morphological were studied. Many growth parameters have been considered to specify the optimum conditions, namely substrate temperature (300 Â°C), oxygen pressure (10-2 Torr), laser fluence energy density (0.4 J/cm2), using double frequency Q-switching Nd:YAG laser beam (wavelength 532nm), repetition rate  (1-6 Hz) and the pulse duration of 10 ns. The results of the X-ray test show that all nanostructures tetragonal are polycrystalline. These results show that grain size increase from 19.5 nm to 29.5 with the increase of annealing temperature. The XRD results also reveal that the deposited thin film, annealed at 400 Â°C of TiO2 have anatase phase. Thin films annealed at 500 Â°C and 600 Â°C have mixed anatase and rutile phases.  Full Width at Half Maximum (FWHM) values of the (101) peaks of these films decrease from 0.450Â° to 0.301Â° with the increase of annealing temperature.  Surface morphology of the thin films have been studied by using atomic force microscopes (AFM). AFM measurements confirmed that the films have good crystalline and homogeneous surface. The Root Mean Square (RMS) value of thin films surface roughness are increased with the increase of annealing temperature